DNMT1 deficiency impacts on plasmacytoid dendritic cells in homeostasis and autoimmune disease - Czéh, Melinda; Stäble, Sina; Krämer, Stephen; Tepe, Lena; Talyan, Sweta; Carrelha, Joana; Meng, Yiran; Heitplatz, Barbara; Schwabenland, Marius; Milsom, Michael; Plass, Christoph; Prinz, Marco; et al. (The journal of immunology, 2022)
Dendritic cells (DCs) are heterogeneous immune regulators involved in autoimmune diseases. Epigenomic mechanisms orchestrating DC development and DC subset diversification remain insufficiently understood but could be important to modulate DC fate for clinical purposes. By combining whole-genome methylation assessment with the analysis of mice expressing reduced DNA methyltransferase 1 levels, we show that distinct DNA methylation levels and patterns are required for the development of plasmacytoid DC and conventional DC subsets. We provide clonal in vivo evidence for DC lineage establishment at the stem cell level, and we show that a high DNA methylation threshold level is essential for Flt3-dependent survival of DC precursors. Importantly, reducing methylation predominantly depletes plasmacytoid DC and alleviates systemic lupus erythematosus in an autoimmunity mouse model. This study shows how DNA methylation regulates the production of DC subsets and provides a potential rationale for targeting autoimmune disease using hypomethylating agents.
Gesehen am 11.05.2022